Multi-Systemic Inflammatory Syndrome in Childhood with Neurological Presentation: A Case Report - Nabeeha N. Akram; Wassan Nori; Khalid Waleed Al qaissi (AlQalam Journal of Medical and Applied Sciences, 2021)
Since the earliest reports of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in China in 2019, COVID 19 has rapidly spread worldwide. Though earliest reports considered children as low risk compared to adults, the pandemic progression unveiled severe COVID-19 in pediatric age groups with different presentations. Furthermore, several serious COVID 19-related consequences in the form of a multisystem inflammatory syndrome (MIS-C) or so-called Kawasaki-like illness have been described in different countries. MIS-C has a wide range of clinical symptoms, including persistent fever, severe malaise, the inclusion of two or more organ systems, laboratory markers of inflammation, and confirmation of SARS-CoV-2 disease in the patients or the patients' contact with a COVID19 positive case. After the patient meets WHO or CDC diagnostic criteria, the diagnosis is typically confirmed. Include fever more than three days with clinical signs of multisystem involvement and elevated markers of inflammation, evidence of SARS-COV-2 infection with no other obvious cause. This report presents a case of MIS-C who presented with aseptic meningitis to highlights the value of testing for COVID-19 in children with new-onset neurological symptoms during the COVID 19 era, especially in the presence of a history of contact with a confirmed case after excluding other apparent causes.